Feeling of psychological cohesion and its relationship to risk perception among kindergarten teacher (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify the feeling of psychological cohesion and its relationship to the perception of risks among kindergarten teachers, as the sample of the research included (200) female kindergarten teachers in the education of Diyala Governorate. Based on previous theories and studies related to the subject of its research, as the scale of feelings of psychological cohesion included (36) items distributed on three dimensions, namely: (feelings of clarity, feelings of voluntariness or will (ability to overcome), feelings of meaning), and the measure of risk perception in its final form included (40 It is divided into four dimensions, namely: (environmental risks, health risks, economic risks, social risks), and the researcher verified the psychometric characteristics of the two research tools, which are: honesty and stability, and the verification of honesty was in two ways: apparent honesty, and constructive honesty, and stability was extracted to measure feelings of psychological cohesion and risk perception By (retest) method, and (Vachronbach equation). After analyzing and processing the data statistically using the statistical bag (spss), the researcher reached the following results: